PERAN PEMERINTAH AMERIKA DALAM PENGEMBANGAN EKONOMI SYARIAH - Amiruddin Kuba (El-Qist: Journal of Islamic Economics and Business (JIEB), 2015)
Today, the development of Islamic economics has impacted not only in moslem countries but also in non moslem countries particularly in United State of America (USA).The evidence of itwhere there is a number of Islamic finance and banking significantly in Indonesia. The progress of Islamic economics is influenced by many factors. One of them is the role of the government in supporting and responding it emergence.Each country has different method and system in responding and to accommodate the emergence of Islamic economics.As a capitalistcountry, the USA has itself challenge to response the emergence of Islamic economics.One of the concernsisrelatedto the sustainability of Islamic economic.Such worriness might be because of some people still think that Islamic economics is Islam itself.While the USA government applies secular system that separate state and religion. On the contrary, a number of people still optimism that the Islamic economics will be developed and accommodated even the USA is the capitalist and secular country.